Synthesis and hepatoprotective properties of Acanthus ilicifolius alkaloid A and its derivatives - LIU, LIN (D.A. Spandidos, 2013)
Acanthus ilicifolius alkaloid A (4-hydroxy-2(3H)benzoxazolone, HBOA) is a naturally occurring compound that has been separated from Acanthus ilicifolius. Previous studies have reported the beneficial effects of HBOA on HSC-T6 cells. This study was undertaken in order to synthesize HBOA and two of its derivatives, specifically, 4-acetoxy-2(3H)-benzoxazolone (AcO-BOA) and 3-acetyl-4-acetoxy-2-benzoxazolone (TC-3), and to investigate the hepatoprotective potentials of these three compounds on CCl(4)-induced liver injury in mice. HBOA was prepared from 2-nitroresorcinol by a 'one pot' reduction and subsequent cyclization with urea. The acyl derivatives, AcO-BOA and TC-3, were prepared from HBOA using a substitution reaction. The compounds were synthesized with good yields (63.08–68.22%). An acute liver injury model was established by administering CCl(4) intraperitoneally to Kunming mice. The mice were then intragastrically administered bifendate (150 mg/kg) or the synthesized compounds at three different doses (200, 100 and 50 mg/kg). The treatment with CCl(4) was observed to increase the levels of aminotransferase (ALT), aspartate aminotransferase (AST), lactic dehydrogenase (LDH) and malondialdehyde (MDA) and decrease the levels of superoxide dismutase (SOD), catalase (CAT), glutathione (GSH) and glutathione peroxidase (Gpx) in the liver tissues of the mice. Furthermore, treatment with CCl(4) elevated the expression level of the proinflammatory mediator TNF-α. However, HBOA and its derivatives attenuated the changes induced by CCl(4). Furthermore, CCl(4)-induced histopathological changes were reduced by treatment with these compounds. These results suggest that HBOA and its acyl derivatives are able to significantly alleviate the hepatotoxicity induced by CCl(4) in mice.